Genome implosion elicits host-confinement in Alcaligenaceae: evidence from the comparative genomics of Tetrathiobacter kashmirensis, a pathogen in the making. - Wriddhiman Ghosh (Public Library of Science (PLoS), 2013)
This study elucidates the genomic basis of the evolution of pathogens alongside free-living organisms within the family Alcaligenaceae of Betaproteobacteria. Towards that end, the complete genome sequence of the sulfur-chemolithoautotroph Tetrathiobacter kashmirensis WT001(T) was determined and compared with the soil isolate Achromobacter xylosoxidans A8 and the two pathogens Bordetella bronchiseptica RB50 and Taylorella equigenitalis MCE9. All analyses comprehensively indicated that the RB50 and MCE9 genomes were almost the subsets of A8 and WT001(T), respectively. In the immediate evolutionary past Achromobacter and Bordetella shared a common ancestor, which was distinct from the other contemporary stock that gave rise to Tetrathiobacter and Taylorella. The Achromobacter-Bordetella precursor, after diverging from the family ancestor, evolved through extensive genome inflation, subsequent to which the two genera separated via differential gene losses and acquisitions. Tetrathiobacter, meanwhile, retained the core characteristics of the family ancestor, and Taylorella underwent massive genome degeneration to reach an evolutionary dead-end. Interestingly, the WT001(T) genome, despite its conserved architecture, had only 85% coding density, besides which 578 out of its 4452 protein-coding sequences were found to be pseudogenized. Translational impairment of several DNA repair-recombination genes in the first place seemed to have ushered the rampant and indiscriminate frame-shift mutations across the WT001(T) genome. Presumably, this strain has just come out of a recent evolutionary bottleneck, representing a unique transition state where genome self-degeneration has started comprehensively but selective host-confinement has not yet set in. In the light of this evolutionary link, host-adaptation of Taylorella clearly appears to be the aftereffect of genome implosion in another member of the same bottleneck. Remarkably again, potent virulence factors were found widespread in Alcaligenaceae, corroborating which hemolytic and mammalian cell-adhering abilities were discovered in WT001(T). So, while WT001(T) relatives/derivatives in nature could be going the Taylorella way, the lineage as such was well-prepared for imminent host-confinement.